Beneficial Effects of Cynaroside on Cisplatin-Induced Kidney Injury In Vitro and In Vivo - Nho, Jong-Hyun; Jung, Ho-Kyung; Lee, Mu-Jin; Jang, Ji-Hun; Sim, Mi-Ok; Jeong, Da-Eun; Cho, Hyun-Woo; Kim, Jong-Choon (Toxicological research (Seoul), 2018)
Anti-cancer drugs such as cisplatin and doxorubicin are effectively used more than radiotherapy. Cisplatin is a chemotherapeutic drug, used for treatment of various forms of cancer. However, it has side effects such as ototoxicity and nephrotoxicity. Cisplatin-induced nephrotoxicity increases tubular damage and renal dysfunction. Consequently, we investigated the beneficial effect of cynaroside on cisplatin-induced kidney injury using HK-2 cell (human proximal tubule cell line) and an animal model. Results indicated that 10 µM cynaroside diminished cisplatin-induced apoptosis, mitochondrial dysfunction and caspase-3 activation, cisplatin-induced upregulation of caspase-3/MST-1 pathway decreased by treatment of cynaroside in HK-2 cells. To confirm the effect of cynaroside on cisplatin-induced kidney injury in vivo , we used cisplatin exposure animal model (20 mg/kg, balb/c mice, i.p., once a day for 3 days). Renal dysfunction, tubular damage and neutrophilia induced by cisplatin injection were decreased by cynaroside (10 mg/kg, i.p., once a day for 3 days). Results indicated that cynaroside decreased cisplatin-induced kidney injury in vitro and in vivo , and it could be used for improving cisplatin-induced side effects. However, further experiments are required regarding toxicity by high dose cynaroside and caspase-3/ MST-1-linked signal transduction in the animal model.